2022
DOI: 10.3390/pharmaceutics15010011
|View full text |Cite
|
Sign up to set email alerts
|

3D Printed Osteoblast–Alginate/Collagen Hydrogels Promote Survival, Proliferation and Mineralization at Low Doses of Strontium Calcium Polyphosphate

Abstract: The generation of biomaterials via 3D printing is an emerging biotechnology with novel methods that seeks to enhance bone regeneration. Alginate and collagen are two commonly used biomaterials for bone tissue engineering and have demonstrated biocompatibility. Strontium (Sr) and Calcium phosphate (CaP) are vital elements of bone and their incorporation in composite materials has shown promising results for skeletal repair. In this study, we investigated strontium calcium polyphosphate (SCPP) doped 3D printed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 55 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…While ceramic-based bone constructs have been used in a large number of studies [46,47], research is still needed to develop scaffolds based on bioresorbable polymers [16]. Previously, we showed that SCPP polymerized alginate/collagen hydrogels facilitate MC-3T3 osteoblast growth and mineralization [48]. However, additional factors such as rigid-ity and essential blood supply are fundamental, especially for bone defects larger than 5 cm [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…While ceramic-based bone constructs have been used in a large number of studies [46,47], research is still needed to develop scaffolds based on bioresorbable polymers [16]. Previously, we showed that SCPP polymerized alginate/collagen hydrogels facilitate MC-3T3 osteoblast growth and mineralization [48]. However, additional factors such as rigid-ity and essential blood supply are fundamental, especially for bone defects larger than 5 cm [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…Collagen offers additional advantages, such as low immunogenicity and the promotion of bone regeneration. The use of collagen matrices has demonstrated the ability to influence osteoblast behavior within diverse hydrogels [33]. To achieve rapid gelation, self-healing post-bioprinting and subsequent stabilization through secondary crosslinking, shear-thinning, and self-healing properties, alginate was subjected to methacrylation and oxidation and then ionically crosslinked through an egg-shell model [34].…”
Section: Hydrogels Used With Calcium Phosphates In 3d Bioprintingmentioning
confidence: 99%
“…On the contrary, chemical hydrogels are less dependent on external stimuli and have a tendency for greater mechanical resistance [ 46 ]. Finally, the swelling of hydrogels reaches a limit once the cohesive and osmotic forces reach equilibrium [ 47 , 48 ].…”
Section: Tissue Engineering For Bioresponsive Hydrogelsmentioning
confidence: 99%
“…Physically crosslinked hydrogels are assembled without the use of chemical modifications or crosslinking materials [ 49 ]. For example, alginate can be crosslinked using divalent cations within a solution [ 48 ]. However, despite these advantages, physical hydrogels have inconsistent performance in vivo due to their inflexibility towards gel pore size, chemical functionalization, and degradation [ 49 ].…”
Section: Tissue Engineering For Bioresponsive Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation